INFORMATION TECHNOLOGY AND CONSUMER BEHAVIOUR IN TOURISM: STUDENT TRAVEL PLANNING BY USING THE INTERNET - Ochoa Siguencia, Luis; Marzano, Gilberto; Herman, Damian (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The increasing competitiveness in the global tourism market and the use of ubiquitous mobile connection to the Internet by young customers encourage tourism operators to invest more in e-promotion and e-resources, in order to increase their business. Accordingly, it is useful to analyse students' expectations to understand their preferences as a potential customer group. This paper presents the first step of an ongoing investigation that focuses on the tourist preferences of university students. We report and discuss the result of a survey conducted involving the students of Sport and Tourism management at the Akademii Wychowania Fizycznego im. Jerzego Kukuczki in Katowice.For our survey, we used “Google form tool” and “Statistica 13” software suite. The χ2 test was used for data analysis. From our research, it emerged that the preferred means of communicating is email for female students whilst telephone for male students; for both Booking.com resulted to be the most popular tourism platform.